Prevalence of Respiratory Symptoms among Ecuadorian Banana Plantation Workers (2019)
Respiratory diseases are a global problem which affect workers as well as the general population. According to the World Health Organization (WHO), it is estimated that 235 million people world-wide suffer from asthma and 64 million from chronic obstructive pulmonary disease (COPD) (World Health Organization). The prevalence of asthma is estimated to be 4%, while the prevalence of wheezing, the main asthma symptom, is around 9% (To et al., 2012). In the workplace, dusts, allergens, and chemicals might cause respiratory symptoms, asthma, and COPD (3). Pesticides, globally used to control pests and known to be toxic to humans as well, were shown to be associated with respiratory outcomes in workers and residents (Doust et al., 2014; Mamane, Baldi, Tessier, Raherison, & Bouvier, 2015; Mamane, Raherison, Tessier, Baldi, & Bouvier, 2015; Mostafalou & Abdollahi, 2017; Nordgren & Bailey, 2016).